Remittance and its Effect on Poverty and Inequality: A Case of Nepal - Salike, Nimesh; Wang, Jingyi; Regis, Paulo (NRB Economic Review, 2022)
This paper examines the impact of remittance on poverty and income inequality in the context of Nepal using cross-sectional national survey- Nepal Living Standard Survey, third edition (NLSS3) of 2010-11. We employ a Heckman two-step estimation model with instrumental variables and constructed counterfactual income to investigate the real impact of remittances. We find that remittance has helped in the reduction of poverty ratio by 5.3% but deepened the poverty gap by 7.37% and severity by 9.25%. In terms of inequality, remittance has helped to reduce inequality within the remittance receiving group, however, it also contributed to rising income inequality when compared to non- remittance receiving group.